2021
DOI: 10.29303/jppipa.v7i2.625
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Search, Solve, Create and Share Learning Models to Improve Students 'Critical Thinking Skills on Acid and Basic Titration Materials

Abstract: This study aims to determine the improvement of students 'critical thinking skills in the acid-base titration material and to know the description of students' responses to learning to search, solve, create, and share. This study used an experimental method, comparing the experimental group with the control group through the pretest-posttest design, carried out at MAN 1 Aceh Barat. The sample selection used purposive sampling technique. The study population was class XI-IPA for the 2019/2020 school year and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
1
5
0
2
Order By: Relevance
“…Students showed that the SSCS learning model was superior to those who did not use it in problemsolving abilities. This presentation is in line with research results [17,18]. They revealed that students' problem-solving ability increased after they experienced the SSCS teaching model compared to those who did not.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Students showed that the SSCS learning model was superior to those who did not use it in problemsolving abilities. This presentation is in line with research results [17,18]. They revealed that students' problem-solving ability increased after they experienced the SSCS teaching model compared to those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…The implementation of SSCS learning is carried out by remote teaching or dare. The results of the research data are presented in Table 2[17].…”
mentioning
confidence: 99%
“…Critical thinking is one of the abilities that must be possessed. It needs to be developed for every student at all levels of education during the learning process at school, and it is necessary to find ways to build this potential (Selman & Jaedun, 2020;Arisa et al, 2021). In today's digital literacy era, students are expected to independently identify a problem, analyze the situation, collect data or information, interpret information, assess something, evaluate, and summarize the information they have generated.…”
Section: Introductionmentioning
confidence: 99%
“…In today's digital literacy era, students are expected to independently identify a problem, analyze the situation, collect data or information, interpret information, assess something, evaluate, and summarize the information they have generated. Students need to observe, experience, reflect, think, or communicate to build or strengthen their beliefs and actions before making relevant decisions (Selman & Jaedun, 2020;van Laar et al, 2020;Arisa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Critical thinking is in the form of thinking that involves reasoning and logic to solve problems (Fuad et al, 2017). Critical thinking is how a person processes information by analyzing, observing, and evaluating before determining whether they reject or accept information (Arisa et al, 2021). In addition, to improve critical thinking skills, students are also required to have independence in learning.…”
Section: Introductionmentioning
confidence: 99%